Cultural Indicators of Development - Terry McKinley (United Nations Research Institute for Social Development (UNRISD), 1997)
The joint UNRISD-UNESCO series of Occasional Papers on Culture and Development is a first step in facilitating and catalyzing an international debate on culture and development based on high-quality research. In the fourth paper, Terry McKinley examines human development from a cultural perspective, focusing on how people's quality of life is determined by how they are able to live together. The paper describes three indices that could be combined into a composite Cultural Index of Development. First, a Cultural Freedom Index could indicate whether a society respects and allows basic human freedoms of belief, thought and expression. Second, a Creative Empowerment Index could indicate whether a society encourages people to express themselves in innovative ways. Thirs, a Cultural Dialogue Index could register the basic opportunities and means for mutually beneficial communication among people of different cultures.
Keywords: 330